2019
DOI: 10.13005/bpj/1747
|View full text |Cite
|
Sign up to set email alerts
|

Male infertility and viral infection: Interference role of the human herpesvirus types (3 – 6) with disturbances effects of some cytokines hypersecretion and seminal oxidative defense system in the infertility etiopathogenesis of some idiopathic infertile Iraqi patients

Abstract: To study the role of potential relationship of chronic human herpes virus types (3 – 6) infection and their correlation with the up-regulation of some cytokines (IL-2, IL-10 and IFN gamma) and effect of (8-OHdG) and (TAOC) levels onto male infertility. A Case – control study with semen samples which were collected by masturbation during the routine semen analysis of a total ninety age-matched participants as; fertile males 35 (38.9%) with proven fertility as a normal semen quality and infertile males 55 (61.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These findings are consistent with the outcomes of other prior investigations. A study conducted byMuhsin et al (2019) shown that there is no statistically significant disparity in age…”
mentioning
confidence: 97%
“…These findings are consistent with the outcomes of other prior investigations. A study conducted byMuhsin et al (2019) shown that there is no statistically significant disparity in age…”
mentioning
confidence: 97%